2021
DOI: 10.1111/tbed.14215
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and pathogenicity assessment of pigeon paramyxovirus type 1 circulating in China during 2007–2019

Abstract: Pigeon paramyxovirus type 1 (PPMV‐1) is an antigenic variant of Newcastle disease virus (NDV) which is mainly associated with infections of pigeons and has the potential to result in disease in chickens. In this study, we characterised 21 PPMV‐1 isolates from diseased pigeons in China during 2007–2019. Phylogenetic analysis revealed that all isolates belonged to genotype VI. Among them, most isolates belonged to sub‐genotype VI.2.1.1.2.2, suggesting that VI.2.1.1.2.2 has become a prevalent genotype in pigeons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…NDV strains of several genotypes have been isolated and detected in pigeons, including genotypes VI, VII, and XXI [16,22,23]. In China, the strains that infect pigeons are mainly of genotype VI [12,[16][17][18]. The two strains also belong to genotype VI, suggesting that genotype VI is the dominant strain in pigeons in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NDV strains of several genotypes have been isolated and detected in pigeons, including genotypes VI, VII, and XXI [16,22,23]. In China, the strains that infect pigeons are mainly of genotype VI [12,[16][17][18]. The two strains also belong to genotype VI, suggesting that genotype VI is the dominant strain in pigeons in China.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed antigenic distinctions between genotype VI and genotype II strains [10][11][12], implying that pigeons immunized with genotype II and genotype IV vaccines may not have complete protection against genotype VI strains. The importance of the continuous surveillance of genotype VI NDV in pigeons has been emphasized in order to accurately monitor its spread and to develop effective control strategies [8,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The serotypes, classes, and genotypes as well as the year of isolation and the source of isolation are indicated: wild birds (W), pigeons (Pi), and poultry (Ch). If the pathogenicity of the virus was established in the cited work, then it is indicated by color: red indicates pathogenic isolates and green indicates non-pathogenic isolates [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , …”
Section: Introductionmentioning
confidence: 99%
“…PPMV-1 is a most dangerous pathogen for doves and pigeons in China (Guo et al, 2013;Wang et al, 2017;He et al, 2020). The PPMV-1 currently circulating in China belongs to genotype VI (Tian et al, 2020;Yu et al, 2022;Zhan et al, 2022). The PPMV-1 SD19 strain used in the present study was isolated in Shandong province from an outbreak in a pigeon yard.…”
Section: Introductionmentioning
confidence: 99%